Effect of Healthy Lifestyle and Balanced Nutrition Education on Knowledge Among Junior High School Students: A One-Group Pretest–Posttest Study - Ahmad Muzakir; Aryadi Rachman; Ramadhan Arifin; Sunarno Basuki (STKIP Pasundan, 2026)
This study aimed to determine the effect of healthy lifestyle and balanced diet education on improving students' knowledge at SMPN 4 Belawang, Barito Kuala Regency. This research employed a quantitative pre-experimental method using a one-group pretest–posttest design. The population consisted of all students at SMPN 4 Belawang, and 55 students were selected using total sampling. Data were collected using a validated knowledge questionnaire administered before and after the educational intervention. Data analysis was performed using descriptive statistics and the Paired Sample t-test. The results showed that the mean knowledge score increased from 58.70 before the intervention to 87.18 after the intervention, with a significant difference (p = 0.000). The findings indicate that healthy lifestyle and balanced diet education effectively improves students' knowledge. Therefore, school-based health education programs are recommended to promote healthy behaviors among adolescents.